The Formulations of Scrub Cream from Non Fermentation Cocoa Powder and The Effects on Skin - Medan Yumas; Sitti Ramlah; Mamang Mamang (Balai Riset dan Standardisasi Industri Pontianak, 2015)
The content of non fermented cocoa powder is phenolic compounds of polyphenols group which protecting skin from ultra violet radiation (UVB). This research aims to determine the concentration of non fermented cocoa powder that capable to protect the skin from UVB. This study used a complete randomized design with a treatment on the concentration of non fermented cocoa powder as the active ingredient of scrub cream. Scrub cream was made from non fermented cocoa powder in a variable concentration 2.5; 3.5; 4.5; 5.5% (w/w) with three replicates. The results showed that the viscosity were 36, 42, 49 and 70 dps, respectively. The four scrub cream have pH value above 5 which fulfilled the standard of SNI 01-3524-1994 and uncontained of Pb and Hg. The most panelists was preferred scrub cream with the concentration of non-fermented cocoa powder 3.5%, it gave moisture and smooth effect also lasted minimum for 180 minutes.